The effect of selection processes on employee turnover in small and medium enterprises in Sunnyside, Pretoria - Okusolubo, Titilola Olusola (My University, 2013)
Employers invest significant time and resources in employee selection. However, the effectiveness of the selection is not routinely measured. One measure of such effectiveness is employee turnover. Often selection processes do not identify the best applicant for the organisation. Employee selection techniques often lead to employee turnover because the focus is on filling vacancies rather than finding the best candidate. The human resources selection process is important to short-term and long-term success of an organisation because employees are generally regarded as the most valued assets. Selecting the candidates that fit best has an important impact on an organisation’s success. A well-designed and implemented selection process is one that optimises the selection process. Bad selection costs organisations significant money because of the need to reinvest in the selection process and new employee training. Selection is also important in order for an organisation to keep its competitive edge. However, affirmative action, equal employment opportunity and diversity are not to be considered separate actions or initiatives in the selection process as they are part of governmental requirements. As such, the increasing attention on human resource management in small and medium enterprises is a comparatively recent phenomenon. Organisations have realised that the continuance of business will depend on the quality and management of the human resources they possess. Research has shown that positioning the right person in the right position is one of the crucial issues in organisations. If this does not happen, the organisation will not only suffer financial losses, but it may also lose its competitive edge. The dearth of research into selection as a human resource practice in SMEs with particular emphasis on their employee turnover is probably due to the fact that HR practitioners, the managers and or owners of the SMEs, often ignore personnel or human resource issues, such as recruitment and selection, training and development, participation-enhancing work designs, formal dispute resolution and employee counseling. The majority of the empirical studies on human resources management practices (HRMP) in small businesses are still in an explorative stage and mainly descriptive. The purpose of this study was to evaluate the effect of the selection processes as a human resource management function on employee turnover in small and medium enterprises in Sunnyside, Pretoria. The research methodology used to conduct the study was a combination of a literature review and an empirical study. A non-probability sampling technique involving judgment and convenience sampling procedures was used. The research instrument was a five-point Likert interval scale, which had forty four items and was pretested with 10 persons who were not related to the research sample. The instrument was revised and a pilot survey of 30 questionnaires was administered to respondents one month prior to the main survey. Sections B, C and D were subjected to reliability analysis and the results indicated that the scale has a high reliability value with Cronbach’s alpha of (0.824), (0.520) and (0.910) for sections B, C and D respectively. The reliability analysis suggested that the scale of items C4, C11 and C12 should be reversed. On doing so the alpha value increased to 0.824. For the main survey, 300 questionnaires were administered of which 210 representing 84% response rate were usable for the data analysis. Furthermore, a descriptive analysis of section A was undertaken. Tables depicting frequencies and percentages were used to describe the demographic information of respondents. Inferential statistics, such as factor analysis and bivariate correlations were undertaken on items in sections B, C and D of the research instrument. The empirical investigation indicated that the effect of selection processes on employee turnover was composed of three underlying factors, namely: factors influencing selection procedures; techniques influencing selection procedures; and aspects effecting employee turnover in SMEs. The selection factors were found to be positively correlated to one another but had a negative correlation with the turnover factor. Significant statistical associations were found to be present between the factors and the size of the organisations, marital status, level of educational qualifications, ethnic classification, the extent of influence of the EEA on selection processes, the belief of what the selection process consists of and the frequency of selection process exercises conducted by the SMEs involved.
M. Tech. (Business Administration, Faculty of Management Sciences): Vaal University of Technology
Keywords: Employee selection; Employee turnover; Human resource management; 658.314096822; Personnel management -- South Africa.; Labor turnover -- South Africa.